The Impact of an Effective Communication Course with Enhanced Student Engagement on Communication Skills and Empathic Tendency of Preservice Teachers - Özge Ceren Çelik, Gülgün Alpan (Educational Process: International Journal)
Background/purpose – The purpose of this study was to examine the impact of an Effective Communication course with enhanced student engagement on preservice teachers’ communication skills and empathic tendency levels.